Biomimicry : innovation inspired by nature - Benyus, Janine M (New York : Quill, 1998)
Science writer and lecturer Janine Benyus names and explains this phenomenon. She takes us into the lab and out in the field with cutting-edge researchers as they stir vats of proteins to unleash their computing power; analyse how electrons zipping around a leaf cell convert sunlight into fuel in trillionths of a second; discover miracle drugs by watching what chimps eat when they$1 (Bre sick; study the hardy prairie as a model for low-maintenance agriculture; and more.s
Echoing Nature How Will We Feed Ourselves How Will We Conduct Business Where Will We Go From Here
Includes bibliographical references (p. [299]-300) and index
Keywords: Technological innovations; Human ecology; Nature